THU0308 Extensive analysis of T cell receptor gamma (TCRG) gene rearrangements reveals a similar repertoire in eosinophilic granulomatosis with polyangiitis (EGPA) and in hypereosinophilic syndrome (HES). (15th June 2017) - Baldini, C; Galimberti, S; Ciabatti, E; Petrini, I; Tarrini, G; Latorre, M; Elefante, E; Ferro, F; Grossi, R; Pisanti, N; Petrini, M; Mosca, M
Abstract : Background: Hypereosinophilia-associated syndromes are a heterogeneous group of diseases characterized by sustained and elevated blood eosinophilia with evidence of eosinophil-induced organ damage. Classically, Eosinophilic granulomatosis with polyangiitis (EGPA) and Hypereosinophilic syndrome (HES) present several overlapping clinical and laboratory features, making it challenging to correctly insert patients in restricted and well-defined categories with specific and more effective therapeutic approaches. Therefore, great efforts are ongoing searching for novel biomarkers able to differentiate these two disorders in daily practice. Objectives: To detect T cell receptor gamma (TCRG) clonal rearrangements in EGPA and HES, comparing the frequency distribution of V region and J region segment utilization in the study population. Methods: In this single center study, we included consecutive patients with a diagnosis of EGPA and HES. Inclusion criteria were: documentation of a persistent peripheral eosinophilic count of ≥1.5 x109/L and signs or symptoms of organ involvement. Clinical and laboratory data of the patients were collected. Sequence-based determination of the frequency distribution of TCRG Gene Rearrangements was performed using next-generation sequencing with the Illumina MiSeq (LymphoTrack TRG assay, Invivoscribe). Results: We included 21 patients (9 with EGPA and 12 with HES). Four EGPA patients were MPO-ANCA positive. We detected TCRG clonal rearrangements in 44% (4/9) patients with EGPA and in 42% (5/12) patients with HES (p-value = n.s). No association was observed between TCRG clonal rearrangements and ANCA status in EGPA patients. Recurrent TCRG gene rearrangements were observed; in particular, Vg10JgP1 (5 cases) and Vg4Jg1/2 (4 cases) were detected in both EGPA and HES, whereas Vg9Jg1/2 (2 cases) and Vg10Jg1/2 (2 cases) were found only in patients with HES. Conclusions: Even if preliminary, this study reveals a similar T cell receptor gamma repertoire in EGPA and HES, thus suggesting a possible antigen-driven inflammatory response underlying hypereosinophilia in both EGPA and HES. Moreover, our results would suggest that the TCR clonality cannot be used as a tool for the differential diagnosis between EGPA and HES. Disclosure of Interest: None declared